Persebaran Cerita Panji dalam Spirit Kenusantaraan - Sumaryono Sumaryono (Institut Seni Indonesia Yogyakarta, 2020)
The Creation of the Character of Xiao Mei in the Play Script of Senja dan Penantian by Hernandes Saranela Inspired by the Chinese Widow Film. The Panji story that appeared around the XIII century at the end of King Airlangga in Singasari, East Java, became popular in the golden age of the Majapahit kingdom. In 1330 Gajah Mada was appointed by King Putri Majapahit Tribhuanatunggadewi as the ‘Mahapatih’ of the Majapahit kingdom. One year later, in 1331, to be precise, Mahapatih Gajah Mada made an oath known as the “Palapa Oath.” The “Palapa Oath” stated, among other things, that Gajah Mada would not enjoy/eat a palapa before “Nusantara” could be unified. As Mahapatih, every effort was made to realize the ideals contained in the “Palapa Oath.” Mahapatih Gajah Mada increasingly found a clear path after Tribhuanatunggadewi died, and was replaced by his first son named Hayam Wuruk. When he was crowned, king Hayam Wuruk was 16 years old. Under the inexperienced ‘Raja Muda,’ Mahapatih Gajah Mada’s power grew even more remarkable. It is even said that the real king of Majapahit was Gajah Mada. Due to the tremendous efforts of Mahapatih Gajah Mada, the expansion of the Majapahit empire was influential in various regions throughout the Archipelago. Furthermore, with a synchronic approach, it can be assumed that the spread and existence of the Panji story in various regions in Indonesia can be considered as traces of Mahapatih Gajah Mada’s expansionary politics in realizing his ideals as pronounced in the famous ‘Palapa Oath.’ As it is known, the distribution of the Panji story then adapted to local cultures, which made the Panji story have various versions. For example, the Panji story’s performance in Central Java, Malay, Lombok, Kalimantan, and even to countries on the Southeast Asian peninsula. So two important things to note are that the spread of the Panji story in various regions is in line with Gajah Mada’s expansionary politics. It contains the spirit of ‘Kenusantaraan.’ Various versions of the Panji story in the multiple areas show the nature of diversity in the Archipelago’s unity, which is centered in the Majapahit Kingdom. That is what inspired the founders of this republic to adopt the philosophy of “BHINEKA TUNGGAL IKA,” including the color of the flag “red and white” derived from “coconut sugar,” which has been known since the Majapahit era.Keywords: the distribution of the Panji story; the Palapa Oath; the Archipelag